Protein Malnutrition in BALB/c Mice: An Experimental Model Resembling Clinical Scenario - D'Souza, Vinitha; RJ, Madhura; Shetty, Meghashree; A., Varsha; Chakraborthy, Anirban; B., Mohana Kumar; A., Veena Shetty; Badanthadka, Murali (Journal of Health and Allied Sciences NU, 2022)
Objectives The study aims to develop a stable malnourished experimental mice model resembling the human population for future experimental studies.Materials and Methodology At weaning, female BALB/c mice are separated into two groups: one receiving a low protein diet (LPD, 10% protein) and the other receiving a commercially available normal pellet diet (ND, 18% protein). Model development and stability were assessed using body mass index (BMI), biochemical parameters such as glucose, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total protein, albumin, total cholesterol, calcium, and phosphorus using serum samples at the 12th and 15th weeks of the study, antioxidant assay, and liver histopathology observation. Antioxidant assay and histopathology observation using liver tissue sample excised after euthanasia.Results LPD mice are categorized under grade I malnutrition based on the body weight change with respect to ND as per the principles of Gomez's classification of malnutrition. A significant long-term decrease in BMI of the malnourished group indicates the development of the stable malnourished model. Elevated serum enzyme levels in the 15th week and decreased antioxidant activity suggest liver injury and oxidative stress at the cellular level in the malnourished group. Histopathology alterations in the liver tissue further strengthen these observations reported in the human population of malnutrition.Conclusion This study confirms the development of a stable malnourished experimental model using a LPD (10% protein). This model may be used to study the role of malnutrition in the pathophysiology of any disease, drug action, and its kinetics in the future.
Keywords: antioxidant assay; BALB/c; BMI; low protein diet; mice model; protein malnutrition